Executive Compensation, Disclosure of Greenhouse Gas Emissions and Firm Value - Dian Agustia; Irawan Purwa Wijaya (AFEBI Accounting Review, 2021)
This study aims to determine the effect of executive compensation on firm value through greenhouse gas emissions disclosure as a mediation variable. Population in this research are firms listed in the Indonesia Stock Exchange (IDX) and published sustainability reports for the period 2015 to 2019. The sample determination in this study used a purposive sampling method and obtained 150 companies. The data analysis technique in this research is using Partial Least Square (PLS) test. This study shows that executive compensation has a significant positive effect on firm value but does not affect greenhouse gas emissions disclosure. Greenhouse gas emissions disclosure has no significant effect on firm value. This research contributes to the relationship of literature about the greenhouse gas emissions being able to mediate partially the effect of executive compensation on firm value. Furthermore, it also addresses greenhouse gas emission and executive compensation using company samples and periods that have not been explored previously.